FORMULATION AND EVALUATION OF FLURBIPROFEN FAST DISINTEGRATING TABLETS USING NATURAL SUPERDISINTEGRANTS - Sarfaraz Mohammed; Sharma, Surendra Kumar; KALPANA KAUCHA; DODDAYYA HIREMATH (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main objective of this research was to formulate Fast disintegrating tablets of Flurbiprofen incorporating superdisintegrants, isolated from natural sources like Plantago ovata (PO) seeds, Lepidium sativum (LS) seeds and agar-agar. Methods: Superdisintegrants were isolated from their natural sources using reported methods. Swelling index and hydration capacity was determined for the natural superdisintegrants to know their disintegration capacity. The tablet formulations were designed using isolated natural superdisintegrants. The powder blends were evaluated for pre-compressional parameters like angle of repose, bulk density, tapped density, carr’s index, and hausner’s ratio. Fast disintegrating tablets were prepared by direct compression method. The compressed tablets were characterized for post compression parameters. Results: All formulations had hardness, friability, weight variation and drug content within the pharmacopoeial limits. The wetting time was 84 to 254 sec, in vitro disintegration time was between 59.2 to 221 sec, and in-vitro drug release was as low as 11.80% (LS1) to a maximum of 98.99% (PO4) after 4 min of study. Among all, optimized formulation was PO4, as it showed good wetting time (84 sec), fastest disintegration time (59.2 sec), dispersion time (135 sec) and drug release of 98.99.% within 4 min. Conclusion: Flurbiprofen FDT’s were successfully developed using isolated natural disintegrants. The natural disintegrants isolated showed promising results and can prove as effective alternative for synthetic disintegrants.